2001
DOI: 10.1080/014608601300035580
|View full text |Cite
|
Sign up to set email alerts
|

FIRST-TIME MOTHERS' AND FATHERS' TRANSITION TO PARENTHOOD: Infant Care Self-Efficacy, Parenting Satisfaction, and Infant Sex

Abstract: The threefold purposes of our study were to determine differences between first-time mothers' and fathers' development of infant care self-efficacy and parenting satisfaction, relationships between mothers' and fathers' infant care self-efficacy and parenting satisfaction, and the effect of infant sex on the development of mothers' and fathers' infant care self-efficacy and parenting satisfaction during the first 4 months following the infant's birth. A convenience sample of 44 couples in a midwestern state co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(36 citation statements)
references
References 14 publications
5
30
1
Order By: Relevance
“…Specifically, women’s childcare self-efficacy declined across the transition when they reported making low childcare contributions, whereas men’s childcare self-efficacy actually increased at low contribution levels. These findings are consistent with prior research showing that new mothers tend to report greater infant care self-efficacy and more parenting satisfaction than new fathers do (Ehrenberg et al, 2001; Elek et al, 2003; Hudson et al, 2001), and they also shed light on the role of childcare contribution levels in predicting these differences over time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, women’s childcare self-efficacy declined across the transition when they reported making low childcare contributions, whereas men’s childcare self-efficacy actually increased at low contribution levels. These findings are consistent with prior research showing that new mothers tend to report greater infant care self-efficacy and more parenting satisfaction than new fathers do (Ehrenberg et al, 2001; Elek et al, 2003; Hudson et al, 2001), and they also shed light on the role of childcare contribution levels in predicting these differences over time.…”
Section: Discussionsupporting
confidence: 90%
“…This greater comfort may also lead women to feel relatively more satisfied with the childcare they do complete (Ehrenberg et al, 2001). Indeed, new mothers report greater infant care self-efficacy and greater parenting satisfaction than new fathers do (Elek, Hudson, & Bouffard, 2003; Hudson, Elek, & Fleck, 2001). Thus, despite the fact that most women engage in significantly more childcare tasks than most men, women’s reactions to these tasks should be more positive than their male partners’ reactions.…”
Section: Individual Differences and Reactions To Childcarementioning
confidence: 99%
“…Studies have shown that parents with multiple children had higher parenting self-efficacy than parents with one child (Leahy-Warren & McCarthy, 2011). Also, parenting selfefficacy increased gradually over the first months after birth in first-time parents (Hudson, Elek, & Fleck, 2001;Porter & Hsu, 2003), consistent with the idea that higher parenting self-efficacy beliefs come with more experience.…”
supporting
confidence: 63%
“…On the one hand, parenting self-efficacy is a critical resource for effective parenting and promotes positive child development (Jones & Prinz, 2005), and new mothers with higher levels of confidence in their parenting abilities may be more willing to open the gate to fathers’ involvement in childrearing via active encouragement. On the other hand, mothers with high levels of parenting self-efficacy, because of their strong confidence in their own approach to parenting, may be more likely to experience frustration when fathers – who tend to have less experience with infants and less confidence in their own parenting (Hudson, Elek, & Fleck, 2001) – care for or engage with their children in ways they do not endorse. Thus, we expected that mothers with greater parenting self-efficacy would be more likely to engage in both types of gatekeeping behavior – reported gate closing as well as gate opening – and would be more likely to hold gate closing attitudes.…”
Section: Introductionmentioning
confidence: 99%